Morally “loaded” labels in the built environment influence perceptions and social judgments - Haga, Andreas (Frontiers in Psychology, 2024)
Products and artifacts with morally loaded labels (e.g., environmentally friendly) appear to influence people's perceptions and behaviors. Previous studies have shown that desktop lamps labeled “environmentally friendly” can enhance perceived color discrimination and improve certain reading activities compared to a physically identical lamp labeled “conventional.” This effect may occur because people tend to align their behavior with moral principles. The present study explored the generalizability and robustness of this label effect by asking participants to make trait judgments of photographed faces. In an experimental design, participants evaluated photos illuminated by a desktop lamp that was either labeled environmentally friendly or not labeled at all. The results revealed that participants assigned more positive traits to individuals in the photographs when the lamp was labeled “environmentally friendly,” particularly those with high altruistic values. The pattern was reversed for participants with low altruistic values. Moreover, participants rated the light from the lamp labeled “environmentally friendly” as more comfortable and claimed that the light increased (perceived) visibility. In conclusion, the source of the light—whether from an environmentally friendly or conventional lamp—affects both the evaluation of the light itself and the judgments made about other individuals. This study explores theoretical explanations for these label effects and discusses their potential implications for pro-environmental interventions.